Age‐related variation and temporal patterns in the survival of a long‐lived scavenger. Issue 2 (14th May 2015) - Chantepie, Stéphane; Teplitsky, Céline; Pavard, Samuel; Sarrazin, François; Descaves, Bruno; Lecuyer, Philippe; Robert, Alexandre
Abstract : Although senescence has been described for various fitness components in a wide range of animal species, few studies have studied senescence in long‐lived species, and little is known about its interactions with varying environmental conditions. Using a 32 year capture–mark–recapture dataset on the griffon vulture Gyps fulvus, we examined the demographic patterns of actuarial senescence and the patterns of year‐to‐year variation in survival rates. We found a significant, surprisingly late, decrease of annual survival probabilities from the age of 28 years onward and divided individual lifetimes into to three categories (juvenile, mid‐age and senescent birds). In agreement with the environmental canalization hypothesis, our analyses uncovered 1) higher temporal variation of annual survival probabilities in both the juvenile and senescent age classes compared to the mid‐age class and 2) low sensitivity of the population growth rate to the survival of both the juvenile and senescent age classes. Our results further suggested that the temporal variation in the survival of senescent birds might be related to intra‐annual changes in air temperature amplitudes. Finally, using population dynamics modeling, we revealed contrasting effects of the inclusion of the senescent age class on predicted population growth, depending on how survival rates were modeled. Altogether, our results demonstrate the existence of a class of senescent birds that exhibit distinct demographic properties compared to juvenile and mid‐age classes.